Shaping the city through food: the historic foodscape of Lisbon as case study - Salvador, M. (Urban Design International, 2019)
One can take cities as palimpsests where environmental, economic and social contexts combine into buildings, streets, public spaces. There is, however, another shaping force: food. Despite being absent from today’s urban planning, historically food systems played an crucial role in shaping pre-industrial cities, defining foodscapes. Food systems have since undergone major transformations, entailing pressing issues that jeopardize sustainable development. European cities provide the perfect lab for new solutions and an historical approach to their foodscapes enables a more holistic knowledge, which may contribute to designing more resilient cities. This article focuses on the foodscape of Lisbon (Portugal) as case study, describing the evolution of the city’s food production spaces, distribution routes and retail spaces, to early twentieth century and to our days. Contemporary strategies and their impact on Lisbon’s foodscape are also highlighted, and, finally, a reflection on how food systems may be explored within urban design, towards more sustainable solutions.